KECENDERUNGAN PARADIGMA POSITIVISME DALAM PENELITIAN MAHASISWA MANAJEMEN PENDIDIKAN ISLAM - Rinda Nurapriliani; Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the dominance of the positivist paradigm in research conducted by Islamic Education Management students, as reflected in the almost exclusive use of quantitative methods. This condition indicates a limited understanding of the relationship between research paradigms, methodologies, and the values of Islamic education. The study aims to describe the tendencies in research method selection among Islamic Education Management students. A descriptive quantitative approach was employed using document analysis and survey techniques. Data were obtained from the Gilib digital repository of UIN Sunan Gunung Djati Bandung and questionnaires administered to 46 active students in the 2024–2025 academic year. The findings reveal that quantitative methods dominated at 98.51%, while qualitative methods accounted for only 1.49%, and no use of mixed methods was identified. Nevertheless, 41.3% of respondents considered mixed methods a more relevant approach. These findings indicate an emerging tendency toward a broader understanding of the integration of research approaches.